Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM112 - Christian Winter; Kathrin Groß; Rachel Barrett; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM112 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 07.10.-14.11.2022 from St. John extquotesingles (Canada) to Cartagena (Colombia) in the Northern and Central Atlantic Ocean. MSM112 focused on the geophysical, sedimentological, and biogeochemical processes of the delta and ROFI, and searched for connections of the river mouth to the La Guajira upwelling system. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project.